2011
DOI: 10.2174/092986711797200462
|View full text |Cite
|
Sign up to set email alerts
|

Evolving Molecular Mechanism-Based Strategies for Control of Hepatocellular Carcinoma

Abstract: Hepatocellular carcinoma (HCC) is a major cause of cancer mortality worldwide. Unresectable or metastatic HCC has a poor prognosis, and systemic cytotoxic chemotherapy has failed to show a substantial benefit for patients with HCC. However, there has been increasing interest in developing novel molecularly targeted agents in HCC due to the accumulation of knowledge of cell signaling and molecular carcinogenesis. Furthermore, some of these agents have proven to be efficacious in other traditionally challenging … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 140 publications
(181 reference statements)
0
4
0
Order By: Relevance
“…Other cells in the liver, such as endothelial cells (Sato and Mori 2011) or BM-MSCs (Garcia, et al 2011) may also be altered due to chronic inflammation or tumorigenesis. Ma et al found that infiltration of monocytes/macrophages might alter the growth and invasion patterns of HCC and that targeting AR in HCC might reduce the infiltration of monocytes/macrophages, thereby suppressing monocyte/macrophage-mediated cancer growth (Wen-Lung Ma, Yin- Yi Chen, Chawnshang Chang, 2013).…”
Section: Part II Androgen/ar Signaling In Liver Cancermentioning
confidence: 99%
“…Other cells in the liver, such as endothelial cells (Sato and Mori 2011) or BM-MSCs (Garcia, et al 2011) may also be altered due to chronic inflammation or tumorigenesis. Ma et al found that infiltration of monocytes/macrophages might alter the growth and invasion patterns of HCC and that targeting AR in HCC might reduce the infiltration of monocytes/macrophages, thereby suppressing monocyte/macrophage-mediated cancer growth (Wen-Lung Ma, Yin- Yi Chen, Chawnshang Chang, 2013).…”
Section: Part II Androgen/ar Signaling In Liver Cancermentioning
confidence: 99%
“…Although the pathogenesis of HCC has been studied at depth, the exact mechanisms and pathways leading to its development are still unclear [1], [2]. A growing body of literature has demonstrated that aberrant lipid metabolic abnormalities may increase the susceptibility of the liver to tumorigenesis [3], [4].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies of patients with liver disease, particularly with HCC, have identified that serum levels of GP73 are more than 30-fold greater than those in patients without the disease (Block et al 2005; Marrero et al 2005). GPC3 is a cell-surface glycoprotein that is absent in the hepatocytes of healthy subjects and patients with hepatitis but highly expressed in hepatocellular cancer cells (Sato and Mori 2011; Jin et al 2012). Several studies have reported that these markers are superior to AFP for the early detection of HCC (Yamamoto et al 2009; Mao et al 2010; Tangkijvanich et al 2010).…”
mentioning
confidence: 99%